Laparoscopic tubal sterilization reversal and fertility outcomes - Jayakrishnan, K (Medknow Publications & Media Pvt Ltd, 2011)
PURPOSE: The purpose of the study was two-fold. Firstly it was to assess the suitability for tubal recanalization and factors predicting successful laparoscopic recanalization. Secondly, it was to analyze the fertility outcomes and factors affecting the pregnancy rate following laparoscopic tubal recanalization. MATERIALS AND METHODS: A retrospective chart review of prospectively followed-up 29 women at a tertiary care center seeking tubal sterilization reversal between May 2005 and February 2010 were included. RESULTS: In 14 (48.3%) women unilateral tubes were suitable and in only 3 women (10.3%) bilateral tubes were suitable. All cases with laparoscopic tubal sterilization were suitable, whereas all cases with fimbriectomy were unsuitable for recanalization. In 6 (20.7%) cases salphingostomy was performed as an alternative procedure to tubal reanastomosis. The overall pregnancy rate was 58.8%. In cases with sterilization by Pomeroy's method, 4 out of 10 (40%) conceived, whereas for laparoscopic tubal ligation cases 6 out of 7 (85.7%) conceived (P=0.32). None of the patients with final tubal length <5 cm conceived (P=0.03). Comparing the age at recanalization, in women ≤30 years, 71.4% conceived, as compared with 50% when age of women was more than 30 years (P=0.37). CONCLUSIONS: The important factors determining the success of recanalization are technique of sterilization and the remaining length of the tube after recanalization. The gynecologist must use an effective technique of sterilization to minimize the failure rates, but at the same time, which causes minimal trauma, and aim at preserving the length of the tube so that reversal is more likely to be successful, should the patient's circumstances change.